Editorial - Gurciullo , Sebastian (Archives & Manuscripts, 2011)
’Does Australia really give a damn about rights?’ was the question journalist and author David Marr addressed in his keynote speech at the Victorian Equal Opportunity and Human Rights Commission’s annual Human Rights Oration on 10 December 2010. With the Australian Government’s decision not to proceed with a Human Rights Act fresh in his mind, Marr reflected on why so many attempts to enshrine human rights into the Australian constitution have now failed to bear fruit. In Marr’s view, the lesson to be drawn from this is that Australians ’contrary to our larrikin myths, are people with deep respect for authority... a tractable, law-abiding people who may loathe politicians, but respect authority. So when it comes to changing the constitution, indeed when it comes to changing any institutions, we only move when we’re told.’ In Marr’s view, the enactment of a human rights bill would only be likely if backed by a consensus of leaders across the political spectrum advocating for such change, rather than through some form of grass-roots agitation. I couldn’t help wondering whether this analysis had something to tell us about the unresolved nature of the Heiner Affair.